2007
DOI: 10.1039/b617036f
|View full text |Cite
|
Sign up to set email alerts
|

Rapid tests for detection and quantitation of Enterococcus contamination in recreational waters

Abstract: Presently, growth-based tests are used for the detection and quantitation of microbiological contaminants in the environment. These tests take a minimum of 24 h to generate a result, which compromises the ability to take the most appropriate action. This report describes a rapid test for Enterococcus in recreational water as an indicator of faecal contamination. This method involves (1) isolation and lysis of the target organism, (2) purification of ribosomal RNA (rRNA) from the lysate and (3) amplification an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…The need for a more rapid estimate of water quality has been repeatedly emphasized by beach mangers, public health officials, and the scientific community. ,,, As a result, U.S. EPA’s recently released 2012 RWQC include the option of monitoring for QENT, a rapid, molecular test for enterococci that can be completed in 4–6 h . Several studies have explored the sample analytical inhibition and related problems associated with the qPCR analysis and have expressed some concern about its relationship to standard culturable indicators, its cost, and its practicality for monitoring programs. , Only a few studies, however, have explored the human health risk end point in relation to the monitoring options available. , The epidemiological studies conducted as part of establishing the 2012 RWQC found a link between QENT concentrations and gastrointestinal illness, ,, but these studies were all conducted at point source impacted beaches.…”
Section: Discussionmentioning
confidence: 99%
“…The need for a more rapid estimate of water quality has been repeatedly emphasized by beach mangers, public health officials, and the scientific community. ,,, As a result, U.S. EPA’s recently released 2012 RWQC include the option of monitoring for QENT, a rapid, molecular test for enterococci that can be completed in 4–6 h . Several studies have explored the sample analytical inhibition and related problems associated with the qPCR analysis and have expressed some concern about its relationship to standard culturable indicators, its cost, and its practicality for monitoring programs. , Only a few studies, however, have explored the human health risk end point in relation to the monitoring options available. , The epidemiological studies conducted as part of establishing the 2012 RWQC found a link between QENT concentrations and gastrointestinal illness, ,, but these studies were all conducted at point source impacted beaches.…”
Section: Discussionmentioning
confidence: 99%
“…The optimization and development of the TMA method for the detection of Enterococcus deliberately spiked into seawater have been described previously (3), and the present study expands on this research to apply the method to a wide range of ambient environmental water samples. The goal of this study was to compare the results obtained with the TMA assay to results obtained with two of the most commonly used reference methods for quantitation of Enterococcus bacteria in water samples, Enterolert (Idexx Laboratories, Inc., Westbrook, ME) and U.S. EPA method 1600 (6), in estuarine, brackish, and storm water samples.…”
mentioning
confidence: 77%
“…The TMA assay has been reported previously to have a good analytical specificity and does not cross-react with the species that are known to cause false positives in the U.S. EPA method. The main advantages of the TMA assay are the rapid time to result (approximately 4 h) and the high level of analytical specificity (3). The data presented here show that TMAbased methods hold promise for use in the future to accurately quantify fecal indicator bacteria in recreational waters.…”
mentioning
confidence: 80%
See 1 more Smart Citation
“…Several studies 8,9,10 have demonstrated that not all ''positive'' isolates from growth-based methods are Enterococci and that such methods are positive for all Enterococcus species. By contrast, it is known that this TMA method is more specific 15 and therefore it might be expected that it would yield a lower rate of positive results than less specific methods in situations where a wide spectrum of microorganisms exists. It is known that storm drains discharge a complex mixture of chemicals and microorganisms and one might anticipate greater variability in the results of such samples.…”
Section: Quantitative Considerationsmentioning
confidence: 98%